Hubungan Pengetahuan Ibu, Pola Makan, dan Pola Asuh Terhadap kejadian karies pada anak usia 4-6 Tahun di PAUD TAAM Al-Ikhlas Sukmajaya Depok Tahun 2022 - Putri Nur Annisa; Rahmat Supriyatna (Jurnal Kesehatan Masyarakat, 2023)
Dental caries is still a major dental and oral health problem, especially in preschool children. The impact of caries is quite serious, which can cause difficulties in chewing, sleeping, and communicating. caries also has an impact on appetite, so it can affect to nutritional status and their physical development. Preschoolers generally not able to maintain their dental health independently, so they still need parents to maintain dental health. this research aims to determine the relationship between Mother's Knowledge, Dietary habit, and Parenting styles with the incidence of caries in children aged 4-6 years at PAUD TAAM Al-Ikhlas Sukmajaya Depok. This research is an observational analytic study with a cross sectional approach. The sampling technique used a total sampling technique which the number of samples was the same as the total population, that is 38 pairs mothers and children respondents. Data collection methods used observation sheets and questionnaires. Analysis of the data used is univariate and bivariate analysis with chi square test analysis to see the relationship between variables. The results showed that on average the mother had good knowledge (57.9%), the dominant child's dietary habit was unhealthy (60.5%), and the democratic parenting styles was the most dominant (86.8%). Then there is a significant relationship on the Dietary habit variable with p-value = 0.007 and Odds Ratio (OR) = 7.125. While the other 2 variables showed no significant relationship, that is the Mother's Knowledge variable with p-value = 0.080 and the Parenting styles variable with p-value = 0.643.